A Fusion Reactor Scheme Using Magnetic Mirrors. (2nd October 2020) - Mazzucato, E.
Abstract: The paper describes a fusion reactor scheme consisting of two 200-m-long magnetic mirrors with a ratio of two connected by semicircular sections to form a racetrack configuration. The two most serious problems of magnetic mirrors, magnetohydrodynamic stability and end losses, are solved by minimizing the negative curvature of the mirror magnetic field lines and using helical windings in the curved sections to add a positive curvature and strong shear to the magnetic field lines at and beyond the mirror throat and for confining the mirror end losses. The reactor should be capable of producing at least 13 GW of fusion power when operating in deuterium-tritium at the same plasma density and temperature as ITER.